2020
DOI: 10.1016/j.jinsphys.2020.104037
|View full text |Cite
|
Sign up to set email alerts
|

Low temperatures impact species distributions of jumping spiders across a desert elevational cline

Abstract: Temperature is known to influence many aspects of organisms and is frequently linked to geographical species distributions. Despite the importance of a broad understanding of an animal's thermal biology, few studies incorporate more than one metric of thermal biology. Here we examined an elevational assemblage of Habronattus jumping spiders to measure different aspects of their thermal biology including thermal limits (CT min , CT max), thermal preference, VĊO 2 as proxy for metabolic rate, locomotor behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Our physiological measurements came from a single population, and it is possible that either cold tolerance or energetic traits differed among populations due to local adaptation or neutral processes (Brandt et al, 2020; Lester & Irwin, 2012; Sinclair et al, 2012). More research is needed to understand how clinal variation in cold tolerance or energetics interacts with exposure to drive sensitivity of a range of species to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Our physiological measurements came from a single population, and it is possible that either cold tolerance or energetic traits differed among populations due to local adaptation or neutral processes (Brandt et al, 2020; Lester & Irwin, 2012; Sinclair et al, 2012). More research is needed to understand how clinal variation in cold tolerance or energetics interacts with exposure to drive sensitivity of a range of species to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…These studies fit into a broader picture of physiological variation in ectotherms. In general, upper physiological limits exhibit less geographic divergence, particularly in terrestrial organisms (e.g., Gaston and Chown 1999;Sunday et al 2011;Brandt et al 2020), a biogeographic pattern known as Brett's rule (Brett 1956;Gaston et al 2009). Likewise, other studies have found higher phylogenetic signal in upper physiological limits than in lower limits (Grigg and Buckley 2013;Hoffmann et al 2013;Gutiérrez-Pesquera et al 2016 signal (by itself) should be interpreted with caution.…”
Section: Rates Of Physiological Evolution Under the Bogert Effectmentioning
confidence: 94%
“…The aminolaevulinic acid is the precursor of protoporphyrin IX (PpIX), it is normally synthesized in mitochondria, thanks to the condensation reaction between glycine and succinyl-CoA [72], but it can also be administrated exogenously as a prodrug [51]. The ALA molecules are better absorbed intracellularly than the PpIX, and their accumulation and photoactivation in porphyrins (PAPs) is higher in cells with greater metabolic activity, such as tumor cells, bacteria, and inflammatory cells [73]. ALADENT device allows, therefore, to maximize the penetration of the PS in the bacterial membrane.…”
Section: Discussionmentioning
confidence: 99%